A thermostable d-polymerase for mirror-image PCR. Issue 7 (2nd February 2017) - Pech, Andreas; Achenbach, John; Jahnz, Michael; Schülzchen, Simone; Jarosch, Florian; Bordusa, Frank; Klussmann, Sven
Abstract: Biological evolution resulted in a homochiral world in which nucleic acids consist exclusively of d -nucleotides and proteins made by ribosomal translation of l -amino acids. From the perspective of synthetic biology, however, particularly anabolic enzymes that could build the mirror-image counterparts of biological macromolecules such as l -DNA or l -RNA are lacking. Based on a convergent synthesis strategy, we have chemically produced and characterized a thermostable mirror-image polymerase that efficiently replicates and amplifies mirror-image (l )-DNA. This artificial enzyme, dubbed d -Dpo4-3C, is a mutant of Sulfolobus solfataricus DNA polymerase IV consisting of 352 d -amino acids. d -Dpo4-3C was reliably deployed in classical polymerase chain reactions (PCR) and it was used to assemble a first mirror-image gene coding for the protein Sso7d. We believe that this d -polymerase provides a valuable tool to further investigate the mysteries of biological (homo)chirality and to pave the way for potential novel life forms running on a mirror-image genome.